Ecomorphological adaptation of Scorpaena porcus (Linnaeus, 1758): evidence from two different environments revealed by sagittae features and somatic growth rates - D’Iglio, Claudio; Famulari, Sergio; Ferri, Josipa; Albano, Marco; Spanò, Nunziacarla; Capillo, Gioele; Savoca, Serena (Frontiers in Marine Science, 2024)
Improve the knowledge base on the ecomorphological adaptation of teleost species to different environments, trying to reconstruct how habitat can shape sagittae, is essential for conservational purposes, evolutionary evaluations, and population dynamics studies. Here is provided a comparative study between sagittae features, growth rates and age composition of two Scorpaena porcus populations inhabiting the Mediterranean waters, one from the Strait of Messina (Central Mediterranean Sea) and one from the Split area (Adriatic Sea). Additionally, the stomach contents of the Messina specimens have also been analysed to provide some preliminary information on the diet of S. porcus. A total of ninety individuals, half from each area, have been obtained from two extremely different environments. Results showed an overall different morphology, shape, and morphometry of sagittae among the size classes of the two investigated populations. Samples from Messina were characterized by a most elliptical and slender shape, with a more regular serration of margins than those from Split, which exhibited a wider sagitta, with a most enhanced anti-rostrum and longer rostrum. Concerning diet, specimens from Messina showed a preference for Crustacea (especially Brachyura and Amphipoda) and Teleost species, showing some differences with literature data from other geographical areas (Split one included). Results have confirmed the reliability of sagittae to detect the inter-population variability of S. porcus from different geographical areas, an essential tool for stock assessment, population studies and investigation on ecomorphological adaptation of teleost species to different habitats.